2021
DOI: 10.1038/s41593-021-00912-7
|View full text |Cite
|
Sign up to set email alerts
|

Divergent projections of the paraventricular nucleus of the thalamus mediate the selection of passive and active defensive behaviors

Abstract: The appropriate selection of reactive and proactive defensive behaviors amid fearful situations is essential for survival. Studies in both rodents and primates have shown that reactive defensive responses depend on the activity of the central nucleus of the amygdala (CeA) whereas proactive ones primarily rely on the nucleus accumbens (NAc). However, the mechanisms underlying flexible switching between CeA-driven (reactive) and NAc-driven (proactive) defensive responses, remain unknown. Here, using a behavioral… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(24 citation statements)
references
References 55 publications
6
18
0
Order By: Relevance
“…Two brain regions, the vSub, located in the temporal lobe ( Gray, 1982 ; Gray and McNaughton, 2000 ; Ito and Lee, 2016 ; Marchant et al, 2016 ; Çavdaroğlu et al, 2021 ), and the PVT, located in the midline thalamus ( Choi and McNally, 2017 ; Zhu et al, 2018 ; Choi et al, 2019 ; Engelke et al, 2021 ; Ma et al, 2021 ), have been implicated in motivational conflict, and so could contribute to these decision-making dynamics. Yet how activity in these brain regions relates to approach–avoidance decision-making remains poorly understood.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two brain regions, the vSub, located in the temporal lobe ( Gray, 1982 ; Gray and McNaughton, 2000 ; Ito and Lee, 2016 ; Marchant et al, 2016 ; Çavdaroğlu et al, 2021 ), and the PVT, located in the midline thalamus ( Choi and McNally, 2017 ; Zhu et al, 2018 ; Choi et al, 2019 ; Engelke et al, 2021 ; Ma et al, 2021 ), have been implicated in motivational conflict, and so could contribute to these decision-making dynamics. Yet how activity in these brain regions relates to approach–avoidance decision-making remains poorly understood.…”
Section: Resultsmentioning
confidence: 99%
“…Many PVT-dependent tasks involve choices between different, incompatible behaviors ( McNally, 2021 ). These include choices between approach and avoid ( Choi and McNally, 2017 ; Choi et al, 2019 ; Engelke et al, 2021 ), between different defensive behaviors (e.g., fight vs flight) ( Ma et al, 2021 ), between approaching different sources of reward (e.g., sign vs goal tracking, Pavlovian to instrumental transfer) ( Campus et al, 2019 ), and between persisting with or ceasing a behavior that no longer yields reward ( Hamlin et al, 2009 ; Otis et al, 2017 ). Like the approach–avoidance choices studied here, these choices necessitate trade-off between the speed and outcome of decision-making.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, PVT1 P neurons integrated to a lesser extent with PFC-projectors (Figure 5c). Interestingly, the medial portion of the pPVT, which lacks PVT2 edge expression and is mostly populated by PVT1 P neurons, is heavily innervated by subcortical inputs which may participate in biasing behavior toward stereotyped emotional reactions like those observed amid imminent environmental threats [84][85][86][87][88]. Additionally, PVT1 P neurons specifically express Esr1 (estrogen receptor 1), a cell marker for ventromedial hypothalamic (VMH) neurons that control aggression and mating, which are stereotyped and conserved behaviors under the control of subcortical networks [89][90][91][92].…”
Section: Discussionmentioning
confidence: 99%
“…The paraventricular nucleus of the thalamus (PVT) is another important area for emotion-based responses, especially fear. The PVT is primarily involved in stress, arousal, and motivated behaviors with projections to the amygdala and limbic cortex ( Kirouac, 2015 ; Azevedo et al, 2020 ; Rowson and Pleil, 2021 ), and it was recently found to mediate PVT-central amygdala freezing responses ( Ma et al, 2021 ). The PVT’s connection to depressive-like behavior is less understood, but reduced tail suspension test immobility with PVT inhibition has been reported ( Kato et al, 2019 ; Barson et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%